Lightweight cryptography for security and privacy : 4th International Workshop, LightSec 2015, Bochum, Germany, September 10-11 2015, revised selected papers /: 4th International Workshop, LightSec 2015, Bochum, Germany, September 10-11 2015, revised selected papers. (2016) - Unknown
No abstract available